Combining ability analysis of some of grain yield stress indices in rapeseed (Brassica napus L.) varieties - Rameeh, Valiollah (Plant Breeding and Seed Science, 2012)
Although most of investigations showed that nitrogen fertilizers gave substantial rapeseed yield increases even in diverse and contradicting conditions but in a few studies were focused on genetic parameters of nitrogen stress effects. Combining ability of some of important grain yield stress indices based on application and non application of nitrogen (N+ and N0) was studied using half diallel of six spring rapeseed varieties and their 15 F2 progenies. Significant mean squares of general and specific combining abilities (GCA and SCA) were observed for potential yield(Yp), Stress yield(Ys), mean productivity (MP), geometric mean productivity (GMP), tolerance index (TOL), stress tolerance index (STI) and stress susceptibility index (SSI), indicating importance of additive and non-additive genetic effects for them. Non significant ratio of GCA to SCA mean square and low narrow-sense heritability estimates were detected for all the indices, indicating the prime importance of non-additive genetic effects. Significant positive GCA effect of Yp, Ys, MP, GMP and STI for PF7045/91 and significant negative GCA effects of them for Option500, indicated the same direction of GCA effects of these indices and GCA effects of Yp and Ys. On compare to SCA effects, most of crosses had significant high parent heterosis for Yp, Ys and and all the stress indices, therefore selection the better combinations based on heterosis will be more effective than SCA effect.